Sky Writings: Air Jamaica’s inflight magazine - Gambrill, Tony; Scott, Dennis (My University, 2003)
Magazine about Jamaica, culture and the people in it.
31 pgs. Typescript, sepia-toned, good condition.
Keywords: Air Jamaica; Air Jamaica - Periodicals; Louise Bennett - 1919-2006; Manners and customs; Jamaica - Description and travel; Jamaica - History; Popular culture - Jamaica; Jamaica - Social life and customs.